The Influence of Academic Supervision Towards Teacher’s Work Disciplines at MTs. Negeri in Musi Banyuasin - Novita, Dewi; Fitria, Happy; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
One of the implementations of learning that requires discipline is academic supervision. The goal of academic supervision is creating conducive and better learning through coaching and enhancing the teaching profession so that there is an assumption that academic supervision affects teacher work discipline. The study aimed to determine and describe whether there was an effect of academic surveillance on teacher work discipline, especially in MTs Negeri in Musi Banyuasin . The hypothesis in this study was that there was an effect of academic supervision towards teachers' work discipline at MTs Negeri in Musi Banyuasin. The data collection method was obtained by using a questionnaire or questionnaire and documentation. The results of the questionnaire or questionnaire data analysis were strengthed by documents proving the effect of academic supervision on teacher work discipline at MTs Negeri in Musi Banyuasin.